A Reconfigurable, Dual-Output INHIBIT and IMPLICATION Molecular Logic Gate - Trifoi, Lavinia A.; Hodgson, Gregory K.; Dogantzis, Nicholas P.; Impellizzeri, Stefania (Frontiers in Chemistry, 2020)
Molecules that respond to input stimulations to produce detectable outputs can be exploited to mimic Boolean logic operators and reproduce basic arithmetic functions. We have designed a two-state fluorescent probe with tunable emission wavelength for the construction of a molecular logic gate with reconfigurable single- or dual-output capability. The system is based on a BODIPY skeleton coupled with 4-(dimethylamino)benzaldehyde. The behaviour of the molecular logic gate can be easily investigated in solution with fluorescence spectroscopy, and the optical readout (fluorescence) can be monitored in one (green) or two (green and red) channels. Depending on the solvent of choice, single INHIBIT or dual INHIBIT/IMPLY logic functions can be achieved using chemical inputs (acid and base). Reconfiguration from single- to dual-output is thus made possible by operating the system in acetonitrile (single output) or toluene (dual output), respectively. The logic gate can be switched by manipulating the fluorescence emission via protonation or deprotonation, even when immobilized onto a glass substrate. At the solid state, the resulting output can be stored for extended periods of time. This feature provides two added benefits: i) memory function and ii) ‘set/reset’ capability of the logic gate. Our design thus provides a proof-of-concept interface between the molecular and electronic domains.